Non‐exposed endoscopic wall‐inversion surgery for an early gastric cancer arising from heterotopic submucosal gastric glands: A case report - Takeshi Abe; Yosuke Toya; Kyohei Sugai; Mizuki Komai; Shunichi Yanai; Haruka Nikai; Shigeaki Baba; Ryo Sugimoto; Naoki Yanagawa; Takayuki Matsumoto (DEN Open)
Abstract A 74‐year‐old man, who was scheduled for surgery against the main duct‐type intraductal papillary mucinous neoplasm of the pancreas, was found to have a subepithelial lesion of the stomach under esophagogastroduodenoscopy. Endoscopic ultrasound‐guided fine needle aspiration for the gastric lesion revealed adenocarcinoma cells. We thus considered carcinomas arising from heterotopic submucosal gastric glands and metastases from the pancreatic lesion as differential diagnoses. We first non‐exposed endoscopic wall‐inversion surgery to the lesion as a total biopsy. The gastric lesion was diagnosed as early gastric cancer originating from heterotopic submucosal gastric glands. The patient subsequently underwent a pylorus‐preserving pancreatoduodenectomy for the intraductal papillary mucinous neoplasm. Our experience suggests non‐exposed endoscopic wall‐inversion surgery is a useful and minimally invasive option for the diagnosis and treatment of gastric submucosal lesions, which are presumed to be malignant in nature.